"Rights and right to participate : demcracy, development, and human rights in post colonial Sri Lanka". - Sri Lanka Foundation Institute. Convention 2003 : Colombo, Sri Lanka); Friedrich-Ebert-Stiftung (Sri Lanka) (Colombo : Friedrich Ebert Stiftung, 2004)
Papers presented at the 3rd Annual Convention of Sri Lanka Foundation Institute, held on 14-15 November 2003 at Colombo.
Title from label mounted on t.p.
"Sri Lanka Foundation (SFL)."
Keywords: Political participation -- Sri Lanka -- Congresses; Democracy -- Sri Lanka -- Congresses; Sri Lanka -- Politics and government -- 1978- -- Congresses